Value stream mapping (VSM) of production line for a high volume manufacturing industry - A.N., Mustafizul Karim; Abd. Rahman, Mohamed (s.n, 2012)
With the limiting resource and tight schedule to meet customer demand, Value Stream Mapping (VSM) has become a valuable tool used by manufacturing companies in streamlining their production processes. In this study, VSM is applied in a metal stamping company that produces LCD TV frames on a built-to-order manufacturing strategy. Based on product flow analysis, a current state VSM is constructed using pertinent data from the production department